1998
DOI: 10.1109/23.736501
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in hardening technologies using shallow-trench isolation

Abstract: Challenges related to radiation hardening CMOS technologies with shallow-trench isolation are explored. Results show that trench hardening can be more difficult than simply replacing the trench isolation oxide with a hardened field oxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(55 citation statements)
references
References 29 publications
2
51
0
2
Order By: Relevance
“…These defects can lead to enhanced radiation-induced charge trapping. It has also been shown that implant damage can cause significant radiation-induced degradation in gate and field oxides [11,16,17]. Thus, it is natural to expect that the very high-fluence implants used to fabricate SIMOX substrates (and some bonded oxide substrates) may cause numerous implant-related defects that might result in enhanced radiationinduced charge trapping in the buried oxide.…”
Section: Buried Oxidesmentioning
confidence: 99%
See 2 more Smart Citations
“…These defects can lead to enhanced radiation-induced charge trapping. It has also been shown that implant damage can cause significant radiation-induced degradation in gate and field oxides [11,16,17]. Thus, it is natural to expect that the very high-fluence implants used to fabricate SIMOX substrates (and some bonded oxide substrates) may cause numerous implant-related defects that might result in enhanced radiationinduced charge trapping in the buried oxide.…”
Section: Buried Oxidesmentioning
confidence: 99%
“…As is the case with gate and field oxides [11], the radiation response of buried oxides has been found to be highly dependent on the fabrication process [12,13]. Two common methods for fabricating SOI substrates are separation by implanted oxygen (SIMOX) and wafer bonding.…”
Section: Buried Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Possible processed induced leakage current path exist for STI, as illustrate fig 1. These paths consist of the corner/ sidewall leakage current path from source to drain in the n channel transistor and these leakage currents are responsible for the degradation in the retention time and power dissipation of logic circuits.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate assessment of effects such as transistor mismatch is not only required by commercial designs using advanced processes, but also required by space applications, since previous work has shown that total ionizing dose (TID) response is sensitive to process variations and layout [1]- [4]. Many space applications rely on commercial foundries to provide advanced process technologies, but how to enhance foundry process design kits (PDKs) accurately and quickly to address the space environment is another challenge.…”
Section: Introductionmentioning
confidence: 99%